ANALISIS PRODUK WISATA TAMAN HUTAN RAYA IR. H. DJUANDA KOTA BANDUNG - Soepardi, Arya Nugraha; Holidin S.W, Gilang; Dienan M, Aulia (JURNAL MEKAR, 2025)
ABSTRACT This research to know dan inform tourism product in Ir. H. Djuanda Great Forest Park that interesting tourist visit this tourism destination. This research based tourism product with three indicators is called 3A consist of tourism attraction, aminities, and accesiblity to interest tourist visit Ir. H. Djuanda Great Forest Park. Product tourism indicator give experience to tourist that they do more activities. Methode in this research is qualitative that discribe and focus product tourism Ir. H. Djuanda Great Forest Park. Data is collected with observation, interview, and documentation. Data is collected form Ir. H. Djuanda Great Forest Park manager about tourism attraction, amenities dan acceseiblity as tourim product component. The result of this research is analysis of Ir. H. Djuanda Great Forest Park tourism product as elemen to interest tourist. From this research can improve tourusm product quality and diversity.